2020
DOI: 10.1186/s12913-020-05632-5
|View full text |Cite
|
Sign up to set email alerts
|

Transnationalism and care of migrant families during pregnancy, postpartum and early-childhood: an integrative review

Abstract: Background: Migrant families' transnational ties (i.e., connections to their countries of origin) may contribute to their hardships and/or may be a source of resiliency. A care approach that addresses these transnational ties may foster a positive identity and give coherence to experiences. We conducted an integrative review to determine what is known about transnational ties and the care of migrant families during pregnancy, postpartum and early childhood. Methods: We searched 15 databases to identify literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 112 publications
0
8
0
2
Order By: Relevance
“…This is not a counter to integration, but to allow migrants and refugees to maintain their transnational identity, and preserve, honour and respect their cultural, religious, and linguistic ties, Salahshour [ 73 ] proposes increased policies and initiative encouraging better intercultural understanding of other minority groups while maintaining the attention given to Māori and Pacific people as being mutually exclusive. Allowing migrants and refugees to maintain their transnational identity and among other identities may provide an alternate and viable avenue to cultivate a sense of belonging, contribute to social and economic capital, and result in the health benefits for migrant and refugee communities as seen elsewhere [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is not a counter to integration, but to allow migrants and refugees to maintain their transnational identity, and preserve, honour and respect their cultural, religious, and linguistic ties, Salahshour [ 73 ] proposes increased policies and initiative encouraging better intercultural understanding of other minority groups while maintaining the attention given to Māori and Pacific people as being mutually exclusive. Allowing migrants and refugees to maintain their transnational identity and among other identities may provide an alternate and viable avenue to cultivate a sense of belonging, contribute to social and economic capital, and result in the health benefits for migrant and refugee communities as seen elsewhere [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also identified resources needed in maternity care to promote health behaviors, including need of cultural awareness. Increased cultural competence has previously been identified as a need in the healthcare meeting for healthcare professionals working with pregnant migrant women and migrant families with young children [ 27 ]. Additionally, we found that resources, such as satisfying communication, time, and trust are essential in the health-promoting meeting.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Laws et al also reported how maternal and child health nurses expressed a desire to know more about how to tailor interactions and recommendations to different cultures [15]. Furthermore, a recent integrative review looking at migrant family experiences also highlighted "the need of culturally safe interventions and care environments", as migrant families reported that the care provided within maternal-and child-healthcare were not always culturally appropriate [26]. Thus, it is important to find working methods that can be adapted to different cultures.…”
Section: Discussionmentioning
confidence: 99%